Mechanical properties of sustainable nano concrete using optimized admixture. (2021) - Danielraj, R. Christopher; Aniruddha, D.N.; Parvati, T.S.; Joanna, P.S.
Abstract: This paper presents the optimization of concrete mixture design to potentially attain the optimum mix. The study thus focusses on the behaviour of concrete with Ground Granulated Blast Furnace Slag (GGBS) and Nano silica (NS) as replacement to cement. Experiments were carried out on specimens with 50% to 80% GGBS and 0% to 2% Nano silica as replacement to cement. Optimization of the proportion was done by implementing the extreme vertex mixture design method for ternary mixture. Based on the extreme vertex mix design method, thirteen mix designs were obtained. Six cubes and six cylinders were cast for each of the thirteen mixes and were tested at the end of 28 days and 56 days to obtain the compressive strength and the split tensile strength. From the results it can be observed that the mix with 49% Ordinary Portland cement, 50% GGBS and 1% Nano silica exhibit 9% more compressive strength than conventional concrete.